The construction of wholesale price index numbers and wholesale price trend in Italy, May 1946-July 1949 - IMPERATORI, M. (PSL Quarterly Review, 2014)
The article analyses the principles used by the Italian Central Institute of Statistics in making the returns and the calculations for compiling the wholesale price index numbers. The enquiry reviews the experience acquired in this matter since 1934-35, and pays particular attention to the difficulties met with and to the expedients adopted to render the new post-war series as uniform as possible with the pre-war series. The last part of the article, dealing with the trend of Italian wholesale prices from May 1946 to July 1949, calls attention to the sometimes parallel, sometimes contrasting features of the price movements, and underlines the progressive attenuation of the phenomenon of price dispersion, which has become more and more apparent in the first half of this year. JEL: E31